Analisis Faktor-Faktor Keamanan Yang Mempengaruhi Dompet Digital di JABODETABEK - Safitry, Julia; Trihandoyo, Agus (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
Since 2014 Bank Indonesia has publicized the National Non-Cash Movement (GNNT), with theaim of building a safe, effective and smooth payment system so that the country's financial systemcan function successfully and efficiently. Digital payment systems in Indonesia are quite diverse,one of which is a digital wallet. However, the increasing use of digital wallets has also potentialdigital security threats that need to be monitored. This study aims to determine what securityfactors influence users in using digital wallets for users in JABODETABEK area. By using adescriptive quantitative approach, the object of this research is the population of JABODETABEKarea who has transacted using digital wallets. Purposive random sampling technique has beenused. Data collection was done though questionnaires in the form of Google Forms, anddistributed via Instagram, Twitter and Whatsapp. This study uses data analysis techniques forclassical assumption tests, multiple linear regression and hypothesis testing, and uses SPSS 25tools for data analysis. The results of the analysis show that the combination of variables, such astransaction speed, authentication, encryption mechanism, software capabilities, protection ofpersonal details and information provided influence the usage of digital wallets, with an influencefactor of 31,1%. Furthermore, authentication, software capabilities, protection of personal detailsand information provided variables influence individually the usage of digital wallets.